2016
DOI: 10.1371/journal.pone.0162546
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Independent Event-Related Desynchronization Responses in Motor-Related Brain Areas to Movement Execution, Movement Imagery, and Movement Observation

Abstract: Electroencephalographic (EEG) event-related desynchronization (ERD) induced by movement imagery or by observing biological movements performed by someone else has recently been used extensively for brain-computer interface-based applications, such as applications used in stroke rehabilitation training and motor skill learning. However, the ERD responses induced by the movement imagery and observation might not be as reliable as the ERD responses induced by movement execution. Given that studies on the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…18.0 (IBM, Chicago, IL). We respectively, examined the effects of group, brain area, test condition, and time-phase on the ERD areas (%) in the mu band (8-12 Hz) and beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Four-way repeated-measures analyses of variance (ANOVA) was used to assess the interactions and the main effects among four variables (group, brain area, condition, and time-phase).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…18.0 (IBM, Chicago, IL). We respectively, examined the effects of group, brain area, test condition, and time-phase on the ERD areas (%) in the mu band (8-12 Hz) and beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Four-way repeated-measures analyses of variance (ANOVA) was used to assess the interactions and the main effects among four variables (group, brain area, condition, and time-phase).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…MT provides visual feedback impressions created by observing the image of the less-affected upper extremity projected over the affected limb. The mechanisms underlying the efficacy of MT include its facilitation of motor learning, promotion of interhemispheric communication and balance between the motor cortices, and increased cortical activation after stroke (3,6,12,15,16). Likewise, mirror visual feedback is thought to restore cortical reorganization, and thereby to improve motor recovery in weak or paralyzed limbs.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of top-down aspect of instruction, which relates to the incorporation of motor imagery (MI; i.e., imagining the execution of an action without physically performing it; Jeannerod, 1994;Hardwick et al, 2018) during AO on the subsequent motor performance has not been fully resolved. From a neural point of view, a partial neural activity overlap was found between AO, MI, and movement execution (Burianová et al, 2013;Kraeutner et al, 2014;Duann and Chiou, 2016;Hardwick et al, 2018;Solomon et al, 2019). According to a recent meta-analysis (Hardwick et al, 2018), AO and MI recruited similar premotor-parietal cortical networks.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that MI exclusively activated areas-the bilateral occipital gyrus, left inferior parietal lobule (IPL), parahippocampus, right superior temporal gyrus, and superior frontal gyrus-that are part of a circuitry important for visuospatial imagery, the processing and remembering of visual scenes, and the representation of three-dimensional space (Epstein and Kanwisher, 1998;Mullaly and Maguire, 2011). Also, EEG studies showed partially resembled event-related desynchronization patterns in movement execution compared to MI and AO (Kraeutner et al, 2014;Duann and Chiou, 2016;Solomon et al, 2019). For example, the magnitude of event-related desynchronization in sensorimotor regions was significantly greater in movement execution than MI during both the preparatory and performance phases .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, motor-related brain 18 activity is manifested in the brain as a specific scenario of neural activity with 19 well-defined frequency and spatial localization. Particularly, it is characterized by event 20 related desynchronization (ERD) in alpha/mu-and beta-bands [9]. The same features 21 are observed during motor imagery in specially trained subjects [10,11].…”
mentioning
confidence: 79%